Reliability in interpreting non-destructive testing (NDT) results of concrete structures - Idrissou, Moumouni Moussa (2006)
This research was carried out to study the reliability in interpreting non-destructive testing results of concrete structures for assessing concrete strength, concrete uniformity, and concrete cover. An experimental research was carried out, involving both destructives and non-destructive testing methods applied to different concrete mixes ranging from 20 to 55 MPa. The specimens consisting of cubes, slabs, and columns were casted for the correlation purposes and as testing samples. Statistical analysis was used to establish a relationship between destructives and non-destructive readings. Direct and predicted values were made on the testing samples and compared. For the strength estimation, the interpretation by cores calibration is more reliable than calibration by cubes. This interpretation can improve by taking calibration specimens from the same batch and cure them in the same conditions as the structures to be investigated. It also appears that the combined pulse velocity and rebound index method has no effect on the accuracy of the interpretation. The interpretation of covermeter data by calibration is reliable and that of the concrete uniformity also; and the use of more than one test method for the latter will increase the confidence on the interpretation.